Coexisting EGFR and TP53 Mutations in Lung Adenocarcinoma Patients Are Associated With COMP and ITGB8 Upregulation and Poor Prognosis - Zheng, Chang; Li, Xuelian; Ren, Yangwu; Yin, Zhihua; Zhou, Baosen (Frontiers in Molecular Biosciences, 2020)
The heterogeneity of lung adenocarcinoma is driven by key mutations in oncogenes. To determine the gene expression, single nucleotide polymorphisms (SNPs), and co-mutations participating in the initiation and progression of lung adenocarcinoma, we comprehensively analyzed the data of 491 patients from The Cancer Genome Atlas. Using log-rank and Kruskal-Wallis analysis, Oncoprint, Kaplan-Meier survival plots, and a nomogram, we found that EGFRL858R with co-mutation TP53 was significant prognostic determinant versus that with co-wild TP53 (hazard ratio, 2.77, P = 0.012). Further gene co-expression network and functional enrichment analysis indicated that co-mutation of EGFRL858R/TP53 increases the expression of COMP and ITGB8, which are involved in extracellular matrix organization and cell surface receptor signaling pathways, thus contributing to poor prognosis in lung adenocarcinoma. Validation was performed using three GEO profiles along with colony formation and CCK-8 assays for proliferation, transwell and wound-healing for migration in transfected H1299 and A549 cell lines. To the best of our knowledge, these results are the first to indicate that patients harboring the co-mutation of EGFRL858R/TP53 show increased expression of COMP and ITGB8, which participate in extracellular matrix dysfunction and can be used as prognostic biomarkers in patients with lung adenocarcinoma.